The Path of AIGC Helping Construct Cultural Digital IPs --Taking the Construction of Hemudu Digital Cultural IP as an Example - Lin, Han; Jia, Weichen (Cultural Arts Research and Development, 2025)
In the context of the digital era, cultural IP design faces the dual challenge of the constraints of traditional creative forms and the imperative for innovative breakthroughs. This paper takes Hemudu culture as the research subject and explores the application path of artificial intelligence generated content (AIGC) technology in digital cultural IP design. Combining cultural gene decoding by multimodal technology, the research utilizes AI language model to assist in building digital cultural IP that possesses robust narrative capabilities, aesthetic expressiveness, and formal innovation. During the design process, by tapping into the deep historical and artistic value of Hemudu culture, the deep integration of culture and technology is successfully realized, and a series of digital cultural IP design results with visual appeal and cultural connotation are initially formed. AIGC technology streamlines and enhances the efficiency of digital cultural IP design, enriches its forms, and empowers the development of digital culture IP industry. The study shows that AIGC technology can significantly improve the efficiency and creativity of digital culture IP design, providing new momentum for the cultural industry. It also reveals the key challenges of standardization and sustainability in the application of the technology. The study provides practical references and theoretical support for promoting the innovative development of digital culture IP industry